Antioxidant Activity of Nutmeg Mace (Myristica fragrans) Graded Extract - Ghina Siti Nurhayati; Dimas Danang Indriatmoko; Erwi Widi Kristiadi; Anisa Fitriani; Tarso Rudiana (Chimica et Natura Acta, 2022)
Nutmeg (Myristica fragrans) contains essential oils and can be applied in industrial scale because it has medicinal benefits such as stimulating the heart system, stomachache, rheumatism, muscle pain, toothache, eliminating toxins in the liver, flatulence, and antioxidant. The purpose of this study was to determine the antioxidant activity of the nutmeg mace graded extract. The research methods include plant determination, sample preparation, extraction by maceration method, phytochemical test, and antioxidant test using the DPPH method. The yield of Mace Nutmeg extract obtained was 30.3% n-hexane, 8.79% ethyl acetate, and 3.79% methanol and the IC50 value of each mace nutmeg extract, namely the n-hexane extract was 56.22±1.15 ppm, 20.39±0.13 ppm ethyl acetate extract and 17.89±0.10 ppm methanol extract. From these results, it can be concluded that mace nutmeg extract has antioxidant activity with a strong category.